Text, Context and Constitutions: Directors’ Fundamental Duties in Aotearoa New Zealand - Barrett, Jonathan (Victoria University of Wellington Law Review, 2025)
This article considers fundamental directors’ duties under the Companies Act 1993. Drawing on fundamental principles of the rule of law, and Roland Barthes’ distinction between lisible and scriptible texts, the article provides a close reading of the text regarding directors’ duties. These duties are then considered in a broader context. An argument is also presented for greater use of bespoke constitutions to establish specific corporate purposes.